Nutrient-regulated control of lysosome function by signaling lipid conversion - Ebner, Michael; Puchkov, Dmytro; Lopez-Ortega, Orestes; Muthukottiappan, Pathma; Su, Yanwei; Schmied, Christopher; Zillmann, Silke; Nikonenko, Iryna; Koddebusch, Jochen; Dornan, Gillian L.; Lucht, Max T.; Koka, Vonda; et al. (Cell, 2023)
Lysosomes serve dual antagonistic functions in cells by mediating anabolic growth signaling and the cata-bolic turnover of macromolecules. How these janus-faced activities are regulated in response to cellular nutrient status is poorly understood. We show here that lysosome morphology and function are reversibly controlled by a nutrient-regulated signaling lipid switch that triggers the conversion between peripheral motile mTOR complex 1 (mTORC1) signaling-active and static mTORC1-inactive degradative lysosomes clustered at the cell center. Starvation-triggered relocalization of phosphatidylinositol 4-phosphate (PI(4) P)-metabolizing enzymes reshapes the lysosomal surface proteome to facilitate lysosomal proteolysis and to repress mTORC1 signaling. Concomitantly, lysosomal phosphatidylinositol 3-phosphate (PI(3)P), which marks motile signaling-active lysosomes in the cell periphery, is erased. Interference with this PI(3)P/PI(4) P lipid switch module impairs the adaptive response of cells to altering nutrient supply. Our data unravel a key function for lysosomal phosphoinositide metabolism in rewiring organellar membrane dynamics in response to cellular nutrient status.
Gesehen am 16.12.2024
Online veröffentlicht: 25. Oktober 2023